Interleukin‐12 and its procoagulant effect on erythrocytes, platelets and fibrin(ogen): the lesser known side of inflammation. (16th November 2017) - Page, Martin J.; Bester, Janette; Pretorius, Etheresia
Summary: Inflammation, with its associated inflammatory molecules, is integral to most chronic diseases, including the various cardiovascular diseases. Interleukin 12 (IL12) is one of the inflammatory cytokines that is upregulated during inflammation; however, we know very little about its exact effect on red blood cells (RBCs), platelets and fibrin(ogen). IL12 is an important pleiotropic cytokine in early inflammatory responses and has potent immunomodulatory, antitumour and anti‐infection activity. Here we investigate how low levels of circulating IL12, comparable to levels found during chronic inflammation, affect coagulation parameters, platelets and RBCs. We used thromboelastography, scanning electron microscopy, refractometery and wide‐field microscopy. Our results show that IL12 caused hypercoagulation, platelet activation and spreading, as well as RBC agglutination. This phenomenon has far‐reaching implications for treatment of the plethora of conditions where IL12 is upregulated, since it suggests aberrant haemorheology as agglutination affects blood flow. This information might be used in future to target the lowering of IL12 in inflammatory conditions, as well as address RBC agglutination.